Encouraging Academic Integrity Through a Preventative Framework - Kalra, Jessica; Vogel, Vicki (Canadian Perspectives on Academic Integrity, 2021)
Through a collaboration between the Teaching and Curriculum Development Centre (TCDC), the Centre for Intercultural Engagement (CIE) and the Academic Integrity and Student Conduct Office, Langara has developed an open access toolkit for educators called “Encouraging Academic Integrity Through a Preventative Framework”. The impetus for developing a toolkit focused on encouraging academic integrity came from increasing requests for support in addressing the challenges of academic misconduct at our institution. This toolkit was developed to provide instructors with methods and examples of activities and assessments that can help students meet academic standards and expectations. This document is divided into four parts: we start with an exploration of the principles of academic integrity as defined by the International Centre for Academic Integrity, and then move on to examine the complexity in expression and perception of academic integrity using a model we call the complexity quadrant. With this model in mind, we discuss strategies for fostering integrity and preventing contraventions of academic integrity standards through the use of different assessment design practices. We propose to present the sections of the toolkit, focusing on the complexity quadrant, using an interactive discussion approach. By the end of the presentation, participants will be able to: Use the complexity quadrant to reframe conversations around academic integrity Describe assessment design practices that encourage academic integrity The e-book is available for free through BC Campus Pressbooks Open Education Resources.